2022
DOI: 10.3389/fchem.2022.1098209
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the design of photocatalytic H2O2 synthesis system

Abstract: Photocatalytic synthesis of hydrogen peroxide under mild reaction conditions is a promising technology. This article will review the recent research progress in the design of photocatalytic H2O2 synthesis systems. A comprehensive discussion of the strategies that could solve two essential issues related to H2O2 synthesis. That is, how to improve the reaction kinetics of H2O2 formation via 2e− oxygen reduction reaction and inhibit the H2O2 decomposition through a variety of surface functionalization methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…However, the industrial scale production to satisfy the growing demand is met by the so-called anthraquinone method. The significant disadvantages of this process include (i) the use of organic solvents, (ii) high energy requirements, and (iii) unwanted side products, which ultimately affect the ecological balance/environmental harmony. ,, Further, noble metal catalyzed (Pd, Pd/Au) H 2 O 2 production by direct combination of H 2 and O 2 is also an alternative but is highly expensive and explosive and needs special attention. , Additionally, the isopropyl alcohol oxidation method requires a huge amount of raw alcohol and suffers separation issues . As a solution, sustainable and environmentally benign photocatalytic H 2 O 2 production is deemed to be the most promising strategy for effective solar to chemical/fuel conversion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the industrial scale production to satisfy the growing demand is met by the so-called anthraquinone method. The significant disadvantages of this process include (i) the use of organic solvents, (ii) high energy requirements, and (iii) unwanted side products, which ultimately affect the ecological balance/environmental harmony. ,, Further, noble metal catalyzed (Pd, Pd/Au) H 2 O 2 production by direct combination of H 2 and O 2 is also an alternative but is highly expensive and explosive and needs special attention. , Additionally, the isopropyl alcohol oxidation method requires a huge amount of raw alcohol and suffers separation issues . As a solution, sustainable and environmentally benign photocatalytic H 2 O 2 production is deemed to be the most promising strategy for effective solar to chemical/fuel conversion.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, several impactful and interesting review articles highlight polarization science within catalytic systems that leads to effective carrier separation and transfer causing robust efficiency. ,, Even the authors’ group has reported one, explaining the basics of piezopolarization and its effect on photocatalysis, focusing preferentially on H 2 evolution . Adding more, Wang et al and Liu et al discussed the detailed charge carrier separation and migration mechanism in piezo/pyro-assisted photocatalytic systems with suitable examples. , Further, Li and group elaborated on the advantages of a polarized surface and polarization during a surface redox reaction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, light-and electricity-driven H2O2 production has attracted considerable attention. Compared with the above two technologies, photocatalytic or electrocatalytic H2O2 production requires only water, oxygen, and sunlight, which is more convenient and environmentally friendly [14][15][16][17][18][19][20][21][22]. Various strategies, such as defect engineering [23], morphology modulation [24], elemental doping [25], single-atom loading [26], heterojunction engineering [27], and the introduction of organic molecules or groups [28], have been used to improve the performance of H2O2 production via photocatalysts or electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%